Interferon‐free therapy of chronic hepatitis C with direct‐acting antivirals does not change the short‐term risk for de novo hepatocellular carcinoma in patients with liver cirrhosis. Issue 4 (4th December 2017) - Mettke, F.; Schlevogt, B.; Deterding, K.; Wranke, A.; Smith, A.; Port, K.; Manns, M. P.; Vogel, A.; Cornberg, M.; Wedemeyer, H.
Summary: Background: Hepatitis C virus (HCV) clearance with IFN‐based therapies reduces the incidence of hepatocellular carcinoma (HCC). There has been some debate if IFN‐free therapy with direct‐acting antivirals alters the risk for HCC. Aim: To investigate the HCC incidence in cirrhotic HCV patients who cleared HCV with direct‐acting antivirals vs untreated controls. Methods: We prospectively monitored 373 patients with chronic hepatitis C who received IFN‐free therapies with direct‐acting antiviral after January 2014. A retrospective control cohort of untreated cirrhotic patients was recruited out of 3715 HCV patients who were followed at our centre between 2007 and 2013, with similar HCC screening protocols. Results: 158 direct‐acting antiviral‐treated and 184 control patients with liver cirrhosis were included in this analysis. The groups did not differ in gender and genotype distribution, severity of liver disease and prevalence of diabetes mellitus. Patients were followed up for a median of 440 (range 91‐908) and 592 (range 90‐1000) days. HCCs developed in 6 and 14 patients during follow‐up, resulting in an incidence of 2.90 vs 4.48 HCCs per 100 person‐years. In the direct‐acting antiviral‐treated group, there was no new case of HCC later than 450 days after treatment initiation. In multivariate analysis, higher MELD‐Scores and AFP‐levels were independently associated with HCC development. Transplant‐free patient survival was similar in both groups. Conclusions: IFN‐free direct‐acting antiviral therapy of chronic hepatitis C does not alter the short‐term risk for HCC in patients with liver cirrhosis. A reduced HCC incidence may become evident after more than 1.5 years of follow‐up. Abstract : Linked Content This article is linked to Kao and Su and Mettke and Wedemeyer papers. To view these articles visit https://doi.org/10.1111/apt.14565 and https://doi.org/10.1111/apt.14582 .